Ezra Pound and Confucianism : Remaking Humanism in the Face of Modernity - Lan, Feng, 1954- (Book collections on Project MUSE., 2005)
"In Ezra Pound and Confucianism, Feng Lan offers the first study of Ezra Pound's project of establishing a Confucian humanism as an alternative to Western modernism. Lan shows that when confronted with what appeared to him a dehumanising modern world, Pound discovered in Confucianism possible solutions to issues that he encountered in language, politics, and religion, which Western intellectual tradition as a whole had failed to provide. By integrating Confucian doctrines with received ideas from Western tradition, Pound developed a humanist discourse and brought it to bear on the historical conditions of his time." "Lan examines the strategies with which Pound reconstructed Confucianism into a systematic modern discourse, focusing on his controversial translation of Confucian scriptures, his rethinking of the nature of language and poetry, his political theory of the individual and the state, and his formulation of an unorthodox spirituality." "Situating Pound's works in diverse cultural, historical, and intellectual contexts, Lan demonstrates that Pound's humanism, despite its frequent divergence from the Confucian canon, gives his poetry an ideological coherence and asserts its relevance to the historical and cross-cultural development of Confucianism in modern times."--Jacket